Environmental Run-off Impact Case Study: The Impact of Development and Campus Development of State Islamic University (UIN) Malang - Mohammad Nawawi; Bambang Rahadi (Natural B, Journal of Health and Environmental Sciences, 2011)
Development and improvement of Islamic State University of Malang will cause landscape changes that will cause increasing of run off. This impact is significant because Malang Islamic University is located in the centre of Malang City. The boundary area of this study are Dinoyo sub district, Ketawanggede sub district, Sumbersari sub district, and Karang Besuki sub district. The time of this research is 2006 until 2007. The aim of research is to predict run off due to development and improvement of Islamic State University of Malang. The result of this research indicates that 1) landscape changes due to construction and conversion of open space, 2) decrease green open space amount 52.39%, 3) amount of infiltrationof rainfall is small, 4) increase run off amount 7.14% n rainy season, 5) increase of flood embankment in the street and community settlement in Sumbersari and Klaseman Villages.